KOMUNIKASI INTERNAL GUNUNG STEEL GROUP DALAM PELAKSANAAN PERAN DAN FUNGSI PUBLIC RELATIONS UNTUK MEMBANGUN REPUTASI - Siahaan, Flora Meliana (Jurnal Public Relations (J-PR), 2021)
ABSTRACT: Ideally every company should be aware of the importance of the role of PR as part of its management system. In it, it must be run by departments, units, divisions with specific programs and evaluations to ensure that all of the company's vision and mission achieve its goals. The purpose of this research is to explore the application of internal communication in implementing the role and function of Public Relations in Building the Reputation of Gunung Steel Group based on the 2016-2017 case study. This study aims to provide an in-depth understanding of the implementation of GSG's public relations, the activities of the public relations function during the aforementioned period and the last. This study uses an interpretive paradigm with advanced case study methods with a qualitative approach using primary data, namely active participant observation and unstructured interviews with key & supporting informants.The results of this study illustrate that GSG does not have public relations as a state of being, but GSG still carries out public relations as a communication technique, and so far GSG public relations practitioners are run by a designated department. The synergy of each department in carrying out every public relations activity at GSG and working with the concept of Management by Objective (MBO), everyone plays a role in building the company's reputation. Driven by a sense of responsibility, loyalty and a high sense of belonging, carry out public relations work in accordance with their respective roles and functions. As a proud result, the internal GSG relationship is very conducive and is said to be "no conflict".